Natural Exponential Graphs

$$ \large y=e^x$$

Natural Exponential Graphs also follow the rule of translations and transformations.

YouTube player

Example 1

Sketch the graphs of $y=e^x$ and $y=-e^x$.
Reflected the $x$-axis.

Natural Exponential Graphs Example 1

Example 2

Sketch the graphs of $y=e^x$ and $y=-e^{-x}$.

Natural Exponential Graphs Example 2

Example 3

Sketch the graphs of $y=e^x$ and $y=e^{-x}$.

Natural Exponential Graphs Example 3

Example 4

Sketch the graphs of $y=e^x$ and $y=e^{x+1}$.
Translated to left.

Natural Exponential Graphs Example 4

Example 5

Sketch the graphs of $y=e^x$ and $y=3 \times e^{x}$.
Multiplied 3 times to the $y$ values.

Natural Exponential Graphs Example 5

Example 6

Sketch the graphs of $y=e^x$ and $y=e^x+1$.
Translated to up.

Natural Exponential Graphs Example 6

Example 7

Sketch the graphs of $y=e^x$ and $y=e^{x-1}$.
Translated to right.

Natural Exponential Graphs Example 7

Example 8

Sketch the graphs of $y=e^x$ and $y=e^{x+1}-1$.
Translated to left and down.

Natural Exponential Graphs Example 8

Example 9

Sketch the graphs of $y=e^x$ and $y=e^x-1$.
Translated to down.

Natural Exponential Graphs Example 9

Example 10

Sketch the graphs of $y=e^x$ and $y=e^{x-1}+1$.
Translated to right and up.

Natural Exponential Graphs Example 10

 

Algebra Algebraic Fractions Arc Binomial Expansion Capacity Common Difference Common Ratio Differentiation Double-Angle Formula Equation Exponent Exponential Function Factorials Factorise Functions Geometric Sequence Geometric Series Index Laws Inequality Integration Kinematics Length Conversion Logarithm Logarithmic Functions Mass Conversion Mathematical Induction Measurement Perfect Square Perimeter Prime Factorisation Probability Product Rule Proof Quadratic Quadratic Factorise Ratio Rational Functions Sequence Sketching Graphs Surds Time Transformation Trigonometric Functions Trigonometric Properties Volume




Your email address will not be published. Required fields are marked *